Cognitive and affective dimensions of waiting time satisfaction in Indonesian spicy noodle chains - Paulus, Ivan; Ardiansyahmiraja, Bobby; Yohanes, Marco; Kajee, Jun (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2025)
This study introduces and conceptualizes the “Spicy Noodle Chain” as a distinct fast-dining category and identifies cognitive satisfaction, rooted in fairness and efficiency, as the primary driver of customer satisfaction and loyalty in fast-paced dining contexts. It examines how waiting time satisfaction influences overall customer satisfaction in Indonesia’s emerging Spicy Noodle Chain segment, a localized evolution of the fast-food industry that remains underexplored in academic research. Using data from 195 respondents analyzed through Partial Least Squares Structural Equation Modelling (PLS-SEM), the study investigates both cognitive and affective dimensions of waiting time satisfaction. The findings reveal that waiting area attractiveness and perceived waiting time significantly influence affective satisfaction, while experience evaluation strongly affects cognitive satisfaction and overall satisfaction. However, affective satisfaction does not significantly influence overall satisfaction, suggesting that emotional responses are less enduring than cognitive judgments. Overall, the results highlight that fairness perceptions and operational efficiency shape customer satisfaction more profoundly than transient emotions, offering new insights into service experience management within fast-dining environments.